Rationale and design of a prospective study evaluating population pharmacokinetics and pharmacodynamics of rivaroxaban in Chinese patients with non-valvular atrial fibrillation - Ming-Ming Yan; Xiao-Qin Liu; Yu-Fei Zhang; Hong-Yan Ding; Ming-Kang Zhong; Chun-Lai Ma (BMJ Open, 2022)
Introduction Rivaroxaban is one of the most commonly used non-vitamin K antagonists for stroke prevention in patients with non-valvular atrial fibrillation (NVAF). Different individual exposures exist for Asian and non-Asian populations, and dose selection is different for Japanese and non-Japanese subjects. Few studies have investigated the pharmacokinetics (PK) and pharmacodynamics (PD) of rivaroxaban in Chinese patients and provided a solid reference for dose selection and individualised therapy.Methods and analysis This is a single-centre prospective study. Rivaroxaban-treated Chinese NVAF patients will be recruited according to predetermined inclusion criteria. Blood samples will be collected from both outpatients and inpatients with different sampling strategies at steady state. Rivaroxaban plasma concentration, factor Xa activity, prothrombin time and single-nucleotide polymorphisms of candidate genes will be evaluated. Follow-up will be conducted following 3 and 6 months after enrolment to collect information about the safety and efficacy outcomes. A nonlinear mixed-effects modelling strategy will be used to develop a population PK-PD model of rivaroxaban.Ethics and dissemination The study has been approved by the Ethics Committee of Huashan Hospital, Fudan University (KY2020-016). The study findings will be submitted to peer-reviewed journals and shared with public health authorities.Trial registration number ChiCTR2100046685.